Factores de riesgo para morbi-mortalidad en el adulto mayor sometido a cirugía abdominal de urgencia. - Saldaña Huaccha, Sandra Paola (2013)
Objective: Determine the risk factors to morbimortality in older patient expose to urgency abdomin al surgery in Belen Trujillo Hospital during the years 2003-2011. Material and Method: Study analytic, observational, retrospective, cases and controls_ The population were integrated by 67 older patient s of 65 years expose to urgency abdominal surgery, established as inc1usion and exclusion criteria and divided into two groups: with and without morbi- mortality. Results: The estadistical analysis about the variables in study were to morbílity: age >75 (OR: 4.22; p<O .Ol), male sex (OR: 2.86; p<0.05), operatory time ;::2 hours (OR: 5.75; p<0.01), terapeutic void ?.6 hours (OR: 2.55; p>0.05), comorbilidy (OR: 5.58; p<0.01), surgical history (OR. 2.8; p<0.05) and related mortality: age >75 (OR: 3.47; p<0.05), male sex (OR: 4.67 ; p<0.05), operatory time 2::2 hours (OR. 1.51; p>0.05), terapeutic void ;::6 hours (OR : 2.08; p>0.05), comorbilidy (OR: 5.08; p<0.0 1), surgical history (OR. 4.48; p<0.0 1), Conclusions: The age, sex, operative time, presence of comorbidities and surgical casework are risk factors for morbidity in the elderly undergo ing emergency abdominal surgery. The age, sex, presence of comorbidities and surgical casework are risk factors for morbidity in the elderly undergoing emergency abdominal surgery.